Product Recalls in the Meat and Poultry Industry: Key Drivers of Supply Chain Efficiency and Effectiveness - Vijaya Chebolu-Subramanian; Gary Gaukler (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
There has been a significant increase in the number, size, and severity of food product recalls in the United States in the past decade. Additionally, the pressure to reduce costs has caused many food supply chains to off-shore production activities, making the logistics of recall events more challenging and costly for these supply chains. Thus, there is a strong need for research that can help identify the determinants and key drivers of supply chain efficiency and effectiveness with respect to food recall events. We focus our investigation on meat and poultry supply chains in the United States. Through an empirical analysis of over 500 recall events recorded in the government tracking database during the 2005-2013 period, we identify and test key factors that impact the product recall process in contemporary food supply chains. We conduct a statistical regression analysis to examine the impact of recall strategy, hazard type and the supply chain entity detecting the hazard on the time to recall and the amount of product recovered at closure. Future work also aims to investigate the impact of supply chain structure, reverse logistics and the potential impact of traceability (e.g., RFID) and condition monitoring (e.g., temperature sensors) on recall outcomes.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; supply chain management; food recalls; meat and poultry industry; safety hazards